RELATIONSHIP BETWEEN PRELOADING FLUID ADMINISTRATION AND INTRAOPERATIVE HYPOTENSION INCIDENTS IN MAJOR SURGERY PATIENTS WITH SPINAL ANESTHESIA - Mitasari, Hanum; Budi Pertami, Sumirah; Sulastyawati, Sulastyawati; Hidayah, Nurul (Indonesian Journal of Applied Health, 2025)
Surgery using spinal anesthesia or Subarachnoid Block (SAB) can cause acute vasodilation due to the blockade of the sympathetic nervous system, which increases the capacity of peripheral blood vessels, thereby reducing venous return and causing acute hypotension. This study aims to determine the relationship between preloading fluids administration and intraoperatif hypotension incidence in major surgery patients with spinal anesthesia. This is a non-experimental quantitative study with a cross-sectional correlation approach. The sampling method used is non-probability sampling with a purposive sampling technique. The instruments used observation sheets, a watch, and a tensimeter/NIBP. The study uses the Chi-square test (?=0.05). The results of this study show that the majority of respondents who were given preloading fluids amounted to 26 respondents (65.4%) from 43 respondents. Meanwhile, those who experienced intraoperatif hypotension amounted to 23 respondents (53.3%) from 43 respondents. The Chi-square test results showed a p-value of 0.004, indicating a significant relationship between preloading fluids administration and intraoperatif hypotension incidence in major surgery patients with spinal anesthesia at Lavalette Hospital. It is hoped that health practitioners, especially anesthesia nurses, will pay attention to preloading fluid needs according to the condition of major surgical patients with spinal anesthesia in preventing intraoperative hypotension.